2015
DOI: 10.1080/19942060.2015.1026432
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulations on the role of channel structure for reactive capillary infiltration

Abstract: It is widely recognized that the structure of porous media is of relevance for a variety of mechanical and physical phenomena. The focus of the present work is on capillarity, a pore-scale process occurring at the micron scale. We attempt to characterize the influence of pore shape for capillary infiltration by means of Lattice Boltzmann simulations in 2D with reactive boundaries leading to surface growth and ultimately to pore closure. The systems under investigation consist of single channels with different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The system of a single channel has also the advantage to ease the comparison with simulations in order to improve the description of the surface reaction [31,32]. Dimensionless numbers are introduced with the aim to assess the accuracy of simulations involving surface growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system of a single channel has also the advantage to ease the comparison with simulations in order to improve the description of the surface reaction [31,32]. Dimensionless numbers are introduced with the aim to assess the accuracy of simulations involving surface growth.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it should be kept in mind that multiphase models overestimate the experimental density ratio between the gas and liquid phases. Previous works addressed the case of linear infiltration for single channels [31,32].…”
Section: Lb Modelsmentioning
confidence: 99%
“…It was even demonstrated that, without chemical reaction, infiltration would not occur [23]. On the other hand the formation of SiC on the capillary walls slows down or even blocks silicon infiltration [22][23][24][25]. Further work needs to be performed on calibrated preforms with a narrow and repeatable pore size range in order to correlate the final material's microstructure with relevant control parameters in MW heating.…”
Section: Resultsmentioning
confidence: 93%
“…It is probable that in the first stage of the process, infiltration is controlled by the reaction at the triple line, and after the SiC interface has been formed, the viscous flow becomes the controlling process. A completely different approach to the process of infiltration is performed by Sergi et al [67,68], in which they use Lattice-Bolztman models to describe infiltration in a single capillary and predict that infiltration distance is proportional to time when considering pore narrowing of the capillary due to the reaction. However, their predictions have not been validated experimentally up to date.…”
Section: The Effect Of Variable Radiusmentioning
confidence: 99%